Minding the source: The impact of mindfulness on source monitoring. (6th April 2017) - Alberts, Hugo J. E. M.; Otgaar, Henry; Kalagi, Janice
Abstract : Purpose: This study addressed the impact of mindfulness on source monitoring. Methods: Participants engaged in a brief mindfulness meditation or received no intervention. Next, all participants watched a video of a crime and were then exposed to misinformation regarding this video. Using a source monitoring test, participants' memory performance was measured. Results: Participants who performed the mindfulness meditation showed better source monitoring compared to controls. Mindfulness practice was not found to enhance memory performance. Conclusions: Mindfulness practice may entail an effective way to circumvent memory distortions due to incorrect source monitoring.